Trade-offs in cotton pest management: Seed treatments suppress pests but reduce the abundance of natural enemies in the arthropod community - Melis Yalçin (PLoS ONE, 2026)
Pesticide seed treatments are widely used to protect crops from early-season pests and diseases; however, their broader ecological effects on arthropod communities and non-target organisms remain insufficiently understood. A two-year field experiment was conducted in a cotton agroecosystem to evaluate the community-level effects of seed-applied clothianidin (CLO) and a fungicide mixture containing azoxystrobin, metalaxyl-m, and fludioxonil (AMF). Changes in arthropod population density and diversity were assessed across taxonomic and community levels. The dominant arthropod families recorded included Nabidae, Miridae, Anthocoridae, Asilidae, Chrysopidae, Cicadellidae, and Coccinellidae. Both seed treatments suppressed key sucking pest groups, particularly Cicadellidae and Miridae; however, a significant reduction in predator abundance was also observed in treated plots. These findings indicate a potential trade-off between effective pest suppression and the conservation of natural enemy populations within the arthropod community. Principal response curve (PRC) analysis further demonstrated treatment-related shifts in arthropod communities over time. The results highlight the importance of considering non-target ecological responses when evaluating the sustainability of prophylactic seed treatments in cotton agroecosystems and emphasize the need for long-term investigations into their impacts on multitrophic interactions.